Waging insurgent warfare lessons from the Vietcong to the Islamic State - Jones, Seth G. (Oxford University Press, 2017)
Insurgencies have been among the most common forms of warfare since before the Cold War ended. This book examines how they begin, how they fight, and how to defeat them.